DYNAMIC GOVERNANCE DALAM PEMBANGUNAN PARIWISATA DI KECAMATAN RUPAT KABUPATEN BENGKALIS - Muhammad Zaki Nashrul Haq; Harapan Tua; Adianto Adianto (Halu Oleo University, 2023)
The development of tourism in the Rupat Subdistrict is experiencing problems, this is due to the development priority in North Rupat Subdistrict because it is considered to have more potential. The limitations of the APBD in development are the reason why not all areas on Rupat Island can be developed simultaneously. So there is a need for cooperation with many parties to develop tourism. The concept of dynamic governance-based tourism development can be applied as a tourism development strategy. This study uses a qualitative descriptive method, the authors conducted interviews, observations, and secondary data references. The writer performs data reduction, data display, and conclusion drawing. The results of this research are tourism development in Bengkalis Regency, a strategy (thinking forward) of policy formulation is carried out as the basis for tourism development for the next 15 years. In addition, the participation of the public and the private sector in tourism development is still low. In the context of Dynamic governance in tourism development in Rupat District based on the drafting of these regional regulations it can be a reference and indicator of successful tourism development in Bengkalis Regency, especially Rupat Island. Considering that Rupat Island is a Strategic Tourism Area for Bengkalis Regency.